2019
DOI: 10.1101/744581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the relationship between estimated foliar fungicide use and soybean yield losses due to foliar fungal diseases in the United States

Abstract: 24Fungicide use in the United States to manage soybean diseases has increased in recent years. The 25 ability of fungicides to reduce disease-associated yield losses varies greatly depending on multiple 26 factors. Nonetheless, historical data are useful to understand the broad sense and long-term trends 27 related to fungicide use practices. In the current study, the relationship between estimated soybean 28 yield losses due to selected foliar diseases and foliar fungicide use was investigated using annual 29… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The ability to scout and monitor fields is potentially more challenging with farms where there are large soybean hectares (e.g., harvest zones 3 and 4). Furthermore, one of our different study showed that the mean per hectare foliar fungicide use was significantly low in high harvest zones while the use was greater in low harvest zones [59]. This could potentially result in poor foliar fungal disease control in high harvest zones, leading to greater economic losses.…”
Section: Plos Onementioning
confidence: 85%
“…The ability to scout and monitor fields is potentially more challenging with farms where there are large soybean hectares (e.g., harvest zones 3 and 4). Furthermore, one of our different study showed that the mean per hectare foliar fungicide use was significantly low in high harvest zones while the use was greater in low harvest zones [59]. This could potentially result in poor foliar fungal disease control in high harvest zones, leading to greater economic losses.…”
Section: Plos Onementioning
confidence: 85%